Phosphorescence detection of manganese(VII) based on Mn-doped ZnS quantum dots - Deng, Pan; Lu, Li-Qiang; Cao, Wei-Cheng; Tian, Xi-Ke (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2017)
The phosphorescent l-cysteine modified manganese-doped zinc sulfide quantum dots (l-cys-MnZnS QDs) was developed for a highly sensitive detection of permanganate anions (MnO4−). l-cys-MnZnS QDs, which were easily synthesized in aqueous media using safe and low-cost materials, can emit intense phosphorescence even though the solution was not deoxygenated. However, the phosphorescence of l-cys-Mn-ZnS QDs was strongly quenched by MnO4− ascribed to the oxidation of l-cys and the increase of surface defects on l-cys-MnZnS QDs. Under the optimal conditions, l-cys-MnZnS QDs offer high selectivity over other anions for MnO4− determination, and good linear Stern-Volmer equation was obtained for MnO4− in the range of 0.5–100μM with a detection limit down to 0.24μM. The developed method was finally applied to the detection of MnO4− in water samples, and the spike-recoveries fell in the range of 95–106%. l-cys-MnZnS QDs were easily synthesized in aqueous media and the intrinsic phosphorescence emissions of l-cys-MnZnS QDs decrease with sequentially increasing concentrations of MnO4− without peak shift. [Display omitted] •L-cys-MnZnS QDs, which were easily synthesized in aqueous media using safe and low-cost materials, can emit intense phosphorescence even though the solution was not deoxygenated.•There are also few reports aimed at MnO4- detection based on phosphorescent QDs.•The developed method was finally applied to the detection of MnO4- in water samples.